IDENTIFICATION AND LIFE CYCLE OF MARINE LEECH ISOLATED FROM CULTURED HYBRID GROUPER IN THE NORTHERN BALI WATERS OF INDONESIA - Ketut Mahardika; Indah Mastuti; Sudewi Sudewi; Zafran Zafran (Indonesian Aquaculture Journal, 2018)
The aims of this study were to identify and to determine life cycle of marine leech isolated from cultured hybrid grouper “cantik” (Epinephelus fuscoguttatus fx E. polyphekadion m) in the northern Bali waters of Indonesia under laboratory conditions. Observation of the life cycle of the marine leech was done using petri-dishes (9 cm in diameter) arranged into two groups. In group-1, a petri-dish was filled with sterile seawater (with water exchange of 50%-60% every two days) and in group-2, a petri-dish was filled with continuous running water. DNA sequence was aligned with the sequences from GenBank by BLAST program. Results of similarity index with GenBank sequence exhibited that the nucleic acid of the marine leech isolated from the hybrid grouper “cantik” showed high similarity (99%) with Zeylanicobdella arugamensis. One adult leech could produce 1-63 eggs. The eggs were developed into morula, blastula, and gastrula within five days. The early phase of the embryo with daily water exchange treatment started on day-6 and hatched into larvae on day-10. The eggs incubated with continuous running water had hatched faster (eight days). However, not all eggs hatched at the same time. Some of the eggs hatched 1-3 days after the first one. Hatching rate of eggs varied from 2.70% to 100%. The newly hatched Z. arugamensis larva has transparent color and length of 1.0-1.5 mm. On day-6, Z. arugamensis larvae were already seen attaching to the body of the fish. The size of the Z. arugamensis larvae ranged between 3-11 mm on day-9. In that stage, they were able to produce eggs. Therefore, we argue that Z. arugamensis only requires 17 to 22 days to develop into the adult stage.